2019
DOI: 10.1002/admi.201901449
|View full text |Cite
|
Sign up to set email alerts
|

Insight into Design of MIL‐125(Ti)‐Based Composite with Boosting Photocatalytic Activity: The Embedded Multiple Fe Oxide Count

Abstract: The metal–organic frameworks (MOFs) exhibit poor stability especially under solution phase and high temperature, which compromises their practical application and functionalized modification. So, it is still challenging and imperative for the development of desirable design for the MOF‐functionalized material. Herein, the rational design and construction of MIL‐125(Ti)‐based Fe oxide composite (HPMIL‐125(Ti)‐Fe) are demonstrated. First, the ideal host HPMIL‐125(Ti) with eligible pore size, great stability, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The flat‐band potential of TiMOFs and Ce/TiMOFs‐0.010 derived from Mott‐Schottky plots are about −0.53 V and −0.44 V versus Ag/AgCl, respectively. So the LOMO of TiMOFs and Ce/TiMOFs‐0.010 can be estimated to be −0.43 and −0.34 V versus normal hydrogen electrode (NHE) [48] . Combined with the bandgap values obtained by Tanc plots, the electronic band structures of the two samples could be plotted and shown in Figure S10.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The flat‐band potential of TiMOFs and Ce/TiMOFs‐0.010 derived from Mott‐Schottky plots are about −0.53 V and −0.44 V versus Ag/AgCl, respectively. So the LOMO of TiMOFs and Ce/TiMOFs‐0.010 can be estimated to be −0.43 and −0.34 V versus normal hydrogen electrode (NHE) [48] . Combined with the bandgap values obtained by Tanc plots, the electronic band structures of the two samples could be plotted and shown in Figure S10.…”
Section: Resultsmentioning
confidence: 99%
“…So the LOMO of TiMOFs and Ce/TiMOFs-0.010 can be estimated to be À 0.43 and À 0.34 V versus normal hydrogen electrode (NHE). [48] Combined with the bandgap values obtained by Tanc plots, the electronic band structures of the two samples could be plotted and shown in Figure S10. The highest occupied molecular orbital (HOMO) of TiMOFs and Ce/TiMOFs-0.010 are about 1.84 and 1.85 V, which are more positive than the potential for water oxidation (1.23 V versus NHE).…”
Section: Photoelectrochemical Propertiesmentioning
confidence: 99%
“…The XRD pattern of the Ti-MOF obtained by the solvothermal method exactly corresponds to the simulation pattern of single crystal diffraction data reported before. 34 The characteristic peaks were obvious, indicating that the Ti-MOF has been successfully synthesized. In the XRD pattern of the Ti-MOF@S composites, the main characteristic peaks of the Ti-MOF were also evident, and the first three strong diffraction lines of sulfur correspondingly appeared without other miscellaneous peaks, which proves that nano-sized Ti-MOF@S composites were successfully prepared.…”
Section: Morphology and Structure Characterizationmentioning
confidence: 95%
“…Finally, a novel inorganic-organic hybrid photocatalyst was prepared. Gao et al [106] reported that MIL-125(Ti) was first transformed into hierarchical porous MIL-125(Ti) (HPMI-125(Ti)) via pyrolysis and Fe2O3 was then adsorbed onto HPMIL-125(Ti) to form HPMIL125(Ti)-Fe.…”
Section: Pyrolysis Methodsmentioning
confidence: 99%